2000
DOI: 10.1093/intimm/12.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Soluble human MHC class I molecules induce soluble Fas ligand secretion and trigger apoptosis in activated CD8+ Fas (CD95)+ T lymphocytes

Abstract: In the present study, we have evaluated the apoptotic effect of soluble human MHC class I (sHLA-I) antigens on CD8(+) T lymphocytes. sHLA-I antigens and beta(2)-microglobulin-free HLA class I heavy chains, isolated from serum, induced apoptosis on phytohemagglutinin-activated CD8(+) T lymphocytes in autologous and allogeneic combinations. The extent of CD8(+) T cell apoptosis depends on the degree of activation, time of incubation with sHLA-I antigens and amount of sHLA-I antigens added to the cultures. Apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 54 publications
6
99
0
Order By: Relevance
“…Like classical sHLA class I antigens (27,28), sHLA-G have been shown by Fournel et al (29) and by one of us (30) to induce apoptosis of activated CD8 + T cells and CD8 + NK cells, although this result has not been confirmed by Hunt (31) who however used recombinant HLA-G in her experiments. Binding to CD8 leads to Fas ligand (L) upregulation, soluble FasL secretion and activated CD8 + cell apoptosis by Fas/sFasL interaction [30].…”
Section: Molecular and Functional Characteristics Of Shla-gmentioning
confidence: 93%
“…Like classical sHLA class I antigens (27,28), sHLA-G have been shown by Fournel et al (29) and by one of us (30) to induce apoptosis of activated CD8 + T cells and CD8 + NK cells, although this result has not been confirmed by Hunt (31) who however used recombinant HLA-G in her experiments. Binding to CD8 leads to Fas ligand (L) upregulation, soluble FasL secretion and activated CD8 + cell apoptosis by Fas/sFasL interaction [30].…”
Section: Molecular and Functional Characteristics Of Shla-gmentioning
confidence: 93%
“…[14][15][16] However, we and others reported that sHLA-I molecules lead to activation-induced apoptosis, in vitro, mediated by synthesis and secretion of FasL and the consequent interaction with Fas expressed by allogeneic and autologous T and natural killer (NK) cells. [17][18][19][20][21] Furthermore, nanomolar concentrations of sHLA-I can prevent both alloreactive clones and primary T-cell cultures from recognizing and lysing their targets. 20 It has been reported that sHLA-I molecules bind to CD8 receptors expressed on cytotoxic effector lymphocytes, that is T and NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Using long-term CD8 + T cell lines, a main role has been attributed to Fas-induced apoptosis if activated by a complete immunogenic antigen [30], or rather to Bim induction by TCR triggering if activated by a partially agonistic antigen [31]. Other studies have shown that soluble HLA molecules induce apoptosis in polyclonal CD8 + human T cell blasts through release of bioactive FasL into the supernatant [32,33]. No data are available on a possible differential regulation of T cell subsets by APO2L/TRAIL or by CD59 ligation, which have been shown to be implicated in the down-modulation of mixed populations of human T cell blasts [12,14].…”
Section: Introductionmentioning
confidence: 99%